Why firewood? Exploring the co-benefits, socio-ecological interactions and indigenous knowledge surrounding cooking practice in rural Nepal. (May 2021) - Bharadwaj, Bishal; Pullar, David; Seng To, Long; Leary, Jon
Highlights: Modern Cooking Solutions (MCS) are often pushed with techno-centric motivations. The co-benefits of Traditional Cooking Practices (TCP) are often overlooked. Findings from a detailed study on Nepal suggest 3 complimentary strategies. 1 Localise MCS by modifying the design to suit cultural and practical needs. 2 Improve TCP to reduce negative effects, as fuel stacking is inevitable. 3 Deliver MCS as part of a holistic array of development interventions. Abstract: This paper applies a social context lens to explore the reasons why households in rural areas of developing countries such as Nepal choose to continue with their Traditional Cooking Practice (TCP). Modern Cooking Solutions (MCS) have many benefits over TCP, but each comes with a set of trade-offs. These co-benefits of TCP are poorly understood – this paper argues that the intricacies of current cooking practices must be explored before attempting to push people towards a new solution. We highlight the differences between household expectations and what MCS deliver to look for opportunities to enhance the provision of modern energy for cooking that is more likely to enable broader and more sustainable adoption in rural areas of Nepal. Our findings suggest three complementary strategies: localise MCS by modifying the design to suit cultural and practical needs; improve TCP to reduce its negative effects, as fuel stacking is inevitable; and deliver MCS as part of a holistic array of development interventions designed around the co-benefits of firewood.